1999
DOI: 10.1038/12043
|View full text |Cite|
|
Sign up to set email alerts
|

The base of the proteasome regulatory particle exhibits chaperone-like activity

Abstract: Protein substrates of the proteasome must apparently be unfolded and translocated through a narrow channel to gain access to the proteolytic active sites of the enzyme. Protein folding in vivo is mediated by molecular chaperones. Here, to test for chaperone activity of the proteasome, we assay the reactivation of denatured citrate synthase. Both human and yeast proteasomes stimulate the recovery of the native structure of citrate synthase. We map this chaperone-like activity to the base of the regulatory parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
245
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 446 publications
(256 citation statements)
references
References 29 publications
7
245
1
3
Order By: Relevance
“…The lid harbors nine other Rpn subunits (Rpn3, Rpn5-9, Rpn11-12 and Rpn15) (Tomko and Hochstrasser, 2011;Wolf and Hilt, 2004). The AAA+ proteins (Rpt1-6) of 19S regulatory complexes selectively bind and unfold substrate proteins, open the gate of 20S core particle and facilitate the vectorial translocation of unfolded substrates into the catalytic chamber for proteolysis (Braun et al, 1999;Smith et al, 2005).…”
Section: Figure 11: the Ubiquitin-proteasome System (Ups)mentioning
confidence: 99%
“…The lid harbors nine other Rpn subunits (Rpn3, Rpn5-9, Rpn11-12 and Rpn15) (Tomko and Hochstrasser, 2011;Wolf and Hilt, 2004). The AAA+ proteins (Rpt1-6) of 19S regulatory complexes selectively bind and unfold substrate proteins, open the gate of 20S core particle and facilitate the vectorial translocation of unfolded substrates into the catalytic chamber for proteolysis (Braun et al, 1999;Smith et al, 2005).…”
Section: Figure 11: the Ubiquitin-proteasome System (Ups)mentioning
confidence: 99%
“…The Rpt2 subunit appears to be the only one required for CP opening and substrate entry (Kohler et al, 2001). Two independent studies attributed another function to the base ATPases, in preventing protein aggregation, by acting as chaperones, and in mediating protein refolding and not unfolding (Braun et al, 1999), and the Rpt5 subunit may also bind polyubiquitin chains as shown by crosslinking studies (Lam et al, 2002).…”
Section: Proteasomementioning
confidence: 99%
“…These degradation signals also serve as both the protease binding site and the degradation initiation site. Finally, the proteasome can interact with misfolded or natively unfolded proteins lacking any known targeting signals in an ubiquitin-independent manner [61,62]. However, the relevance of this interaction to protein degradation is not clear.…”
Section: Targeting Signals In the Primary Sequence Of The Substratesmentioning
confidence: 99%